Flow Analysis of Brinkman-Viscoelastic Fluid in Boundary Layer Region of Horizontal Circular Cylinder - Siti Farah Haryatie, Mohd Kanafiah; Abdul Rahman, Mohd Kasim; Syazwani, Mohd Zokri; Nur Syamilah, Arifin; Zati Iwani, Abdul Manaf (Semarak Ilmu Publishing, 2022)
This paper examines the flow of Brinkman-viscoelastic fluid in the boundary layer re-gion. The flow over a Horizontal Circular Cylinder (HCC) is investigated theoretically. The proposed model’s governing equations, which are partial differential equations (PDEs), are transformed to their simplest form by using the appropriate non-dimen-sional variables and non-similarity transformation. The numerical computations for the obtained equations are then computed using the Keller-box method (KBM) which is programmed in MATLAB R2019a software. The velocity distribution results, together with the coefficient of skin friction are presented. A comparison study with previously published results is carried out to ensure that the current findings are accurate. It is discovered that the presence of the Brinkman and viscoelastic parameters influences the velocity behaviour of fluid, with a tendency to decrease the velocity distribution of fluid. Furthermore, both parameters have the potential to decrease the skin friction coefficient. The output can be used as a starting point for complex flow problems that occur frequently in engineering applications.